Sidestream characteristics in water resource recovery facilities: A critical review. (1st April 2023) - Devos, Perrine; Filali, Ahlem; Grau, Paloma; Gillot, Sylvie
Highlights: The review provides concentration ranges for sidestream characteristics in WWRFs. THP mainly affects COD and N content in anaerobic digestion sidestream. The effect of THP on P is not significant due to precipitation inside AD. A list of characteristics to measure before selecting sidestream processes is given. Abstract: This review compiles information on sidestream characteristics that result from anaerobic digestion dewatering (conventional and preceded by a thermal hydrolysis process), biological and primary sludge thickening. The objective is to define a range of concentrations for the different characteristics found in literature and to confront them with the optimal operating conditions of sidestream processes for nutrient treatment or recovery. Each characteristic of sidestream (TSS, VSS, COD, N, P, Al 3+, Ca 2+, Cl −, Fe 2+/3+, Mg 2+, K +, Na +, SO4 2−, heavy metals, micro-pollutants and pathogens) is discussed according to the water resource recovery facility configuration, wastewater characteristics and implications for the recovery of nitrogen and phosphorus based on current published knowledge on the processes implemented at full-scale. The thorough analysis of sidestream characteristics shows that anaerobic digestion sidestreams have the highest ammonium content compared to biological and primary sludge sidestreams. Phosphate content in anaerobic digestion sidestreams depends on the type of applied phosphorus treatment but is also highly dependent on precipitation reactions within the digester. Thermal Hydrolysis Process (THP) mainly impacts COD, N and alkalinity content in anaerobic digestion sidestreams. Surprisingly, the concentration of phosphate is not higher compared to conventional anaerobic digestion, thus offering more attractive recovery possibilities upstream of the digester rather than in sidestreams. All sidestream processes investigated in the present study (struvite, partial nitrification/anammox, ammonia stripping, membranes, bioelectrochemical system, electrodialysis, ion exchange system and algae production) suffer from residual TSS in sidestreams. Above a certain threshold, residual COD and ions can also deteriorate the performance of the process or the purity of the final nutrient-based product. This article also provides a list of characteristics to measure to help in the choice of a specific process. Graphical abstract: Image, graphical abstract